Readability and understandability of clinical research patient information leaflets and consent forms in Ireland and the UK: a retrospective quantitative analysis. Issue 9 (3rd September 2020) - O'Sullivan, Lydia; Sukumar, Prasanth; Crowley, Rachel; McAuliffe, Eilish; Doran, Peter
Abstract : Objectives: The first aim of this study was to quantify the difficulty level of clinical research Patient Information Leaflets/Informed Consent Forms (PILs/ICFs) using validated and widely used readability criteria which provide a broad assessment of written communication. The second aim was to compare these findings with best practice guidelines. Design: Retrospective, quantitative analysis of clinical research PILs/ICFs provided by academic institutions, pharmaceutical companies and investigators. Setting: PILs/ICFs which had received Research Ethics Committee approval in the last 5 years were collected from Ireland and the UK. Intervention: Not applicable. Main outcome measures: PILs/ICFs were evaluated against seven validated readability criteria (Flesch Reading Ease, Flesh Kincaid Grade Level, Simplified Measure of Gobbledegook, Gunning Fog, Fry, Raygor and New Dale Chall). The documents were also scored according to two health literacy-based criteria: the Clear Communication Index (CCI) and the Suitability Assessment of Materials tool. Finally, the documents were assessed for compliance with six best practice metrics from literacy agencies. Results: A total of 176 PILs were collected, of which 154 were evaluable. None of the PILs/ICFs had the mean reading age of < 12 years recommended by the American Medical Association. 7.1% of PILs/ICFs were evaluated as 'Plain English', 40.3%: 'Fairly Difficult', 51.3%: 'Difficult' and 1.3%: 'Very Difficult'. No PILs/ICFs achieved a CCI > 90. Only two documents complied with all six best practice literacy metrics. Conclusions: When assessed against both traditional readability criteria and health literacy-based tools, the PILs/ICFs in this study are inappropriately complex. There is also evidence of poor compliance with guidelines produced by literacy agencies. These data clearly evidence the need for improved documentation to underpin the consent process.